Neurogenic Hypertension Mediated Mitochondrial Abnormality Leads to Cardiomyopathy: Contribution of UPRmt and Norepinephrine-miR- 18a-5p-HIF-1α Axis - Nandi, Shyam S.; Katsurada, Kenichi; Mahata, Sushil K.; Patel, Kaushik P. (Frontiers in Physiology, 2021)
1. Abstract: Aims: Hypertension increases the risk of heart disease. Hallmark features of hypertensive heart disease is sympathoexcitation and cardiac mitochondrial abnormality. However, the molecular mechanisms for specifically neurally mediated mitochondrial abnormality and subsequent cardiac dysfunction are unclear. We hypothesized that enhanced sympatho-excitation to the heart elicits cardiac miR-18a-5p/HIF-1α signaling that lead to mitochondrial abnormalities and consequent pathological cardiac remodeling. Methods and Results: Using a model of neurogenic hypertension (NG-HTN), induced by intracerebroventricular (ICV) infusion of Ang II (NG-HTN; 20ng/min, 14 days, 0.5µl/h, or Saline; Control, 0.9%) through osmotic mini-pumps in Sprague-Dawley rats (200-300g), we attempted to identify a link between sympathoexcitation (norepinephrine; NE), miRNA and HIF-1α signaling to produce mitochondrial abnormalities resulting in cardiomyopathy. Cardiac remodeling, mitochondrial abnormality and miRNA/HIF-1α signaling were assessed using histology, immunocytochemistry, electron microscopy, Western blotting or RT-qPCR. NG-HTN demonstrated increased sympatho-excitation with concomitant reduction in miRNA-18a-5p and increased level of HIF-1α in the heart. Our In-silico analysis indicated that miR-18a-5p targets HIF-1α. Direct effects of NE on miRNA/HIF-1α signaling and mitochondrial abnormality examined using H9c2 rat cardiomyocytes showed NE reduces miR-18a-5p but increases HIF-1α. Electron microscopy revealed cardiac mitochondrial abnormality in NG-HTN, linked with hypertrophic cardiomyopathy and fibrosis. Mitochondrial unfolded protein response (UPRmt) was decreased in NG-NTN indicating mitochondrial proteinopathy and proteotoxic stress, associated with increased mito-ROS and decreased mitochondrial membrane potential (ΔΨm), and oxidative phosphorylation. Further, there was reduced cardiac mitochondrial biogenesis and fusion, but increased mitochondrial fission, coupled with mitochondrial impaired TIM-TOM transport and UPRmt. Direct effects of NE on H9c2 rat cardiomyocytes also showed cardiomyocyte hypertrophy, increased mitochondrial ROS generation, and UPRmt corroborating the in-vivo data. Conclusions: In conclusion, enhanced sympatho-excitation suppress miR-18a-5p/HIF-1α signaling and increased mitochondrial stress proteotoxicity, decreased UPRmt leading to decreased mitochondrial dynamics/OXPHOS/ΔΨm and ROS generation. Taken together, these results suggest that ROS induced mitochondrial transition pore opening activates pro-hypertrophy/fibrosis/inflammatory factors that induce pathological cardiac hypertrophy and fibrosis commonly observed in neurogenic hypertension.